CHARACTERIZATION OF THE LIVER IN JAUNDICE PATIENTS USING ULTRASOUND - Muzafar, Saba; Ali, Abid; Maqsood, Mahnoor; Irram, Saadia; Ashraf, Nadia; Kalsoom, Um-e-; Mazhar, Mehlab; Noor, Ayesha (Medical Science Journal for Advance Research, 2023)
Jaundice is the accumulation of a large amount of circulating bilirubin in the liver. It can be caused by an excessive amount of red cell damage, an inability to eliminate bilirubin from the blood, or a restriction in the liver’s ability to release bile. The jaundice is investigated by using the ideal screening method of an abdominal ultrasound. Objective: To evaluate the liver in jaundice patient using ultrasound. Methods: The study was carried out in a private hospital in Tehsil Kharian, district Gujrat, Pakistan. Data was obtained from December 2023 to March 2023. A sample size of 100 patients was considered using a convenient sampling approach. The patient provided informed consent before the data was collected, which was done in accordance with the ethical standards outlined by the research committee. SPSS version 20.0 was used to enter and analyze the data. Results: The current study shows that jaundice most commonly affects 40-50 year age group. Jaundice patients having a liver size more than 15cm are 48% indicates hepatomegaly while the liver size less than 10cm are 15%. In this study, 20% of patients with jaundice had an irregular liver shape. Conclusion: Ultrasonography is a reliable, and primary method for diagnosing jaundice in young children and elderly people. ultrasound provided significant details regarding changes that took place in the gallbladder, CBD, liver’s size, shape, and echotexture